(untitled) (Development Service Industry Management, 2025)
This article examines how AI can improve the effectiveness of e-commerce marketing strategy. Integration of AI into the marketing strategy of e-commerce companies allows achieving the set goals more accurately and efficiently, and the use of machine learning helps to predict consumer behavior and model market conditions. Artificial intelligence provides fast and accurate analysis of key factors such as consumer behavior and market dynamics, which helps to develop effective marketing strategies to attract and retain customers. The article also discusses the positive and negative aspects of implementing artificial intelligence technologies in the digital marketing strategy of an enterprise. The introduction of AI in the field of e-commerce opens up a strategic advantage in terms of interaction with the target audience of the enterprise. Based on the results of the study, it can be determined that artificial intelligence has a great impact on the company’s ability to compete in its market, increases consumer engagement, which in turn increases conversion. In the work, emphasizes limitations and provides suggestions for future research on similar topics, and also discusses the importance of big data analysis and machine learning for strategic decision-making in e-commerce. The results allow us to realize how the integration of artificial intelligence can change modern marketing and bring significant benefits.